Differences of Microglia in the Brain and the Spinal Cord - Xuan, Fang-Ling; Chithanathan, Keerthana; Lilleväli, Kersti; Yuan, Xiaodong; Tian, Li (Frontiers in Cellular Neuroscience, 2019)
Microglia were previously regarded as a homogenous myeloid cell lineage in the mammalian central nervous system (CNS). However, accumulative evidences show that microglia in the brain and SC are quite different in development, cellular phenotypes and biological functions. How microglia differ between these two regions and whether such diversity may contribute to CNS development and functions as well as neurological diseases will be discussed here.